Analysis of the state of water sources for human consumption and the performance of rural aqueducts in La Soledad river basin, Honduras - Reyes Ponce, K.Y. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica),2006